Investigation of ecological features of acute diarrheal infection pathogens - Malysh, N; Holodilo, E; Chemych, N (Annals of Mechnikov’s Institute, 2020)
Introduction. Microbiocenosis of human body also differs in extreme multicomponents and diverse content of microflora representatives forming its part. According to the biotype of bacterial contamination certain inter-bacterial relations are formed, which is reflected in the qualitative and quantitative characteristics of appropriate microbial landscape. Analysis of numerous microbial association manifestations allows evaluating changes in the pathogen properties influenced by associative microbiota. Work objective - based on the study ecological features of microorganisms isolated from intestine of patients with acute intestinal infections and apparently healthy people, identify potential risk factors for diarrheal infections. Materials & methods. A retrospective epidemiological analysis of acute diarrheal infections incidence was conducted during 2004-2013, using the statistics of the Main Department of the State Sanitary and Epidemiological Service of Ukraine in Sumy region. The intestinal microflora of 93 patients with acute diarrheal infections and 60 persons of the control group (apparently healthy people). As the result 130 bacterial cultures were allocated. Permanence rate was used to estimate biocenosis. Relationships between microbiocenosis members were investigated by determining degree of bond conjunction in associations, using Jaccard coefficient (g). Results & discussion. In 2005-2014 acute diarrheal infection incidence rates of Sumy region population were within 163.7 - 193.6 per 100 people without tendency to decrease. Acute intestinal infections and food toxicoinfections caused by opportunistic pathogens and viruses (p<0.05) dominated in nosological structure. In 35.5 % of cases diarrheal infections were of polyetiological nature. Noroviruses in associations with Candida bacteriaand fungi most often occurred (p<0.05) in the intestinal biotypes. Permanence rate of K. pneumonia, noroviruses, S. aureus, C. albicans was the highest and was accordinly 23.6; 21.5; 19.4 and 19.4 %. C. albicans (88.9 %), noroviruses (80 %), S. thyphimurium (80 %), P. aeruginosae (75 %), E. cloacae (75 %), S. aureus (72.2 %), K. pneumonia (68.2 %), rotaviruses (66.7 %) had average and high associativity coefficient values. The most part of associated causative agents (p<0.05) had antagonistic relations. Stable bacterial associations were formed between noroviruses and K. pneumonia, noroviruses and S. typhimurium, noroviruses and P. aeruginosae (g respectively 36.4; 40.0; 40.0 %). C. albicans, K. pneumoniae, S. aureus, E. cloacae were isolated from healthy people feces in diagnostically significant degree of contamination 43.3 % of cases. The permanence coefficient rated respectively 26.7; 20.0; 20.0; 3.3 %, as well as the associativity coefficient was 90.0; 50.0; 83.3; 100 %. K. pneumonie and S. aureus (g=42.9 %), S. aureus and C. albicans (g=33.3 %) cultures showed the greatest strength of microbial relations. Conclusion. In the process of microorganism co-existence different kinds of relations are formed between them - competitive or cooperative, and as the result the specific microsymbiocenosis is formed according to them. Having established universal common factors of this microsymbiocenosis, you can find ways to protect body from infection.